2019
DOI: 10.1152/jn.00264.2019
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol rapidly modulates excitatory synapse properties in a sex- and region-specific manner in rat nucleus accumbens core and caudate-putamen

Abstract: Estradiol acutely facilitates sex differences in striatum-dependent behaviors. However, little is understood regarding the underlying mechanism. In striatal regions in adult rodents, estrogen receptors feature exclusively extranuclear expression, suggesting that estradiol rapidly modulates striatal neurons. We tested the hypothesis that estradiol rapidly modulates excitatory synapse properties onto medium spiny neurons (MSNs) of two striatal regions, the nucleus accumbens core and caudate-putamen in adult fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 83 publications
5
51
0
Order By: Relevance
“…Quantifying DHHC expression and activity across development will be necessary to test this hypothesis further. Striatal neurons are also known to be sensitive to perinatal aromatization (Bonansco et al, 2018; Cao et al, 2016), and sensitive to fluctuations in sex steroid hormones in adulthood (Krentzel, Barrett, & Meitzen, 2019; Meitzen et al, 2018; Proano, Morris, Kunz, Dorris, & Meitzen, 2018; Willett et al, 2019; Wissman, May, & Woolley, 2012), though not in gross anatomical attributes (Meitzen et al, 2011; Wong, Cao, Dorris, & Meitzen, 2016). Aromatization of testosterone to estradiol early in life may also play a role in males, though this question requires further exploration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantifying DHHC expression and activity across development will be necessary to test this hypothesis further. Striatal neurons are also known to be sensitive to perinatal aromatization (Bonansco et al, 2018; Cao et al, 2016), and sensitive to fluctuations in sex steroid hormones in adulthood (Krentzel, Barrett, & Meitzen, 2019; Meitzen et al, 2018; Proano, Morris, Kunz, Dorris, & Meitzen, 2018; Willett et al, 2019; Wissman, May, & Woolley, 2012), though not in gross anatomical attributes (Meitzen et al, 2011; Wong, Cao, Dorris, & Meitzen, 2016). Aromatization of testosterone to estradiol early in life may also play a role in males, though this question requires further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship between aromatase and extranuclear ER expression is similar to other brain areas exhibiting known rapid estradiol signaling such as the hippocampus of rodents (Kim, Szinte, Boulware, & Frick, 2016; Oberlander & Woolley, 2016; Sato & Woolley, 2016; Tabatadze et al, 2013; Tuscher et al, 2016) and the auditory forebrain of songbirds (Ikeda et al, 2017; Krentzel et al, 2018; Krentzel, Ikeda, Oliver, Koroveshi, & Remage‐Healey, 2019; Remage‐Healey, Dong, Chao, & Schlinger, 2012; Remage‐Healey, Dong, Maidment, & Schlinger, 2011; Saldanha et al, 2000). Overall, the pattern of increased estrogen‐producing cells and a change in the phenotype of estrogen‐sensitive cells suggests that the striatum transforms in adulthood into a region targeted by rapid, neuromodulatory mechanisms of estrogenic signaling (Krentzel, Barrett, & Meitzen, 2019; Meitzen et al, 2018; Yoest, Quigley, & Becker, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, like in many of the regions discussed above, estrogen exposure also regulates spine density in the NAc ( 198 , 199 ). These effects seem to be region-specific within the striatum, as estrogenic effects on spine density and excitatory synaptic properties observed in the NAc were not seen in the caudate-putamen ( 197 , 198 ). The effects of gonadal hormones on NAc physiology is not limited to females, as long-term treatment with androgens in males also modulates NAc dendritic spine density ( 200 ).…”
Section: Reward Systemsmentioning
confidence: 93%
“…VTA dopaminergic neuron basal firing rate is enhanced and more dopamine released into the NAc during behavioral estrus ( 193-195 ). Several electrophysiological properties of NAc medium spiny neurons have been reported to either vary across the estrous cycle or to be rapidly modulated by estradiol exposure ( 192 , 196 , 197 ). Furthermore, like in many of the regions discussed above, estrogen exposure also regulates spine density in the NAc ( 198 , 199 ).…”
Section: Reward Systemsmentioning
confidence: 99%
“…Neural E2 exerts an important role in LTP induction in the nucleus striatum with E2 receptors diffusely expressed in the basal ganglia (Creutz and Kritzer, 2004;Krentzel et al, 2019). Electrophysiological experiments performed in neurons of the dorsal striatum of the male rat showed that E2 synthesis and ER activation are required for the induction of LTP in both spiny projection neurons (SPNs) and cholinergic interneurons because the pharmacological inhibition of P450 aromatase or antagonism of ERs completely prevented the LTP induction of SPNs with no effect on LTD or synaptic depotentiation (Tozzi et al, 2015).…”
Section: Neural E2 Affects Striatal Ltpmentioning
confidence: 99%